Analisis Kemampuan Literasi Membaca Pada Siswa Kelas V Di SDN Inpres Simpasai Kecamatan Lambu Kabupaten Bima - Ariani, Ariani; Salahuddin, Muhammad; Haris, A.; Juliawan, Rizcky (Universitas Pahlawan Tuanku Tambusai, 2025)
Reading literacy skills at SDN Inpres Simpasai, Lambu District, Bima Regency are still low due to the lack of motivation from parents and from several other factors. The purpose of this study is to study and describe students' reading literacy skills as measured through reading literacy indicators in grade V students at SDN Inpres Simpasai. This type of research is a qualitative research using a descriptive method. This research data is in the form of words, sentences, and paragraphs. The data was sourced from teachers and students of grade V at SDN Inpres Simpasai, the cematan lambu of Bima Regency. The data collection techniques in this study include observation, interview, and documentation techniques. The data analysis technique uses Miles and Huberman's descriptive and interactive analysis techniques. Based on the results of the analysis, it can be concluded that students' reading literacy skills are good. Reading skills can be categorized into four categories, (1) the category of poor reading can be 1 student with a percentage of 2.94%, (2) quite good there are 3 students with a percentage of 9.82%, (3) good there are 12 students with a percentage of 36.29%, and (4) very good there are 18 students with a percentage of 53.94%. Reading comprehension ability includes indicators (1) not understanding the text read, there are 6 students with a percentage of 17.64%, (2) very low reading ability, there is 1 student with a percentage of 2.94%, (3) difficulty concentrating in reading letters or words, there are 5 students with a percentage of 14.70%, (4) lack of understanding punctuation, there are 6 students with a percentage of 17.64%, (5) unable to explain the text read, there were 8 students with a percentage of 23.52%, (6) difficulty remembering the text read,there were 8 students with a percentage of 23.52%.